2018
DOI: 10.1002/gps.5036
|View full text |Cite
|
Sign up to set email alerts
|

Cost‐effectiveness analysis of English memory assessment services 2 years after first consultation for patients with dementia

Abstract: Objectives: This paper aims to compare changes over 2 years in patients' healthrelated quality of life (HRQL) with the health and social care costs of diagnosis and treatment of people newly referred to memory assessment services (MAS). Methods:We analysed observational data from 1318 patients referred to 69 MAS who completed resource use and HRQL questionnaires at baseline 3, 6, 12, and 24 months. We reported mean differences in HRQL (disease-specific DEMQOL and generic EQ-5D-3 L), quality-adjusted life years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…To encourage early diagnosis and support for dementia, Memory Assessment Services (MAS) have been implemented in many high-income countries and consist of an integrated, multi-professional approach to diagnosis and management of dementia ( Gomes et al 2019 ). MAS however are not uniformed, meaning they work differently in many localities ( Prince et al 2016 ).…”
Section: Current Practice In Referring To the Memory Assessment Servicesmentioning
confidence: 99%
“…To encourage early diagnosis and support for dementia, Memory Assessment Services (MAS) have been implemented in many high-income countries and consist of an integrated, multi-professional approach to diagnosis and management of dementia ( Gomes et al 2019 ). MAS however are not uniformed, meaning they work differently in many localities ( Prince et al 2016 ).…”
Section: Current Practice In Referring To the Memory Assessment Servicesmentioning
confidence: 99%
“…Emerging evidence also suggests that early detection of MCI may provide an economic benefit to healthcare systems. Although this has been investigated less extensively in individuals with MCI than in individuals with dementia, published literature suggests that the financial burden associated with caring for MCI patients is significant and that routine cognitive assessment may be cost effective (12)(13)(14)(15)(16). Tong et al investigated screening for MCI and dementia by PCPs in England and reported that PCP use of the Mini-Mental State Examination (MMSE), 6-Item Cognitive Impairment Test and the General Practitioner Assessment of Cognition (GPCOG) led to more quality-adjusted life-years (QALYs) than informal PCP assessment alone (i.e., observing individual cognitive ability) (12).…”
Section: Benefits Of Early Detection Of MCImentioning
confidence: 99%